Factors associated with preparedness of the US healthcare system to respond to a pediatric surge during an infectious disease pandemic: Is our nation prepared? - Anthony, MD, Christy; Thomas, BS, Tito Joe; Berg, MPH, Bridget M.; Burke, PhD, MPH, Rita V.; Upperman, MD, FAAP, FACS, Jeffrey S. (American Journal of Disaster Medicine, 2017)
Objective: Recent incidents have demonstrated that the US health system is unprepared for infectious pandemics resulting in a pediatric surge. Development of efficient plans and a structured and coordinated regional response to pediatric pandemic surge remains an opportunity. To address this gap, we conducted a literature review to assess current efforts, propose a response plan structure, and recommend policy actions. Design: A literature review, utilizing MEDLINE and PubMed, through March 2017 identified articles regarding infectious disease pandemics affecting the US pediatric population. After review of current literature, a proposed response plan structure for a pediatric pandemic surge was designed. Results: Inclusion and exclusion criteria reduced an initial screening of 1,787 articles to 162 articles. Articles ranged in their discussion of pediatric pandemic surge. Review of the articles led to the proposal of organizing the results according to 4 S's; (1) Structure, (2) Staff, (3) Stuff (Resources), and (4) Space. Conclusion: The review has supported the concern that the US health system is unprepared for a pediatric surge induced by infectious disease pandemics. Common themes suggest that response plans should reflect the 4Ss and national guidelines must be translated into regional response systems that account for local nuances.